2022
DOI: 10.1111/jdi.13859
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diabetes mellitus has borne much fruit in the prevention of cardiovascular disease

Abstract: Cardiovascular (CV) disease is the most alarming complication of diabetes mellitus (DM), and a strategy aiming at cardiovascular event prevention in diabetes mellitus has long been debated. Large landmark clinical trials have shown cardiovascular benefits of intensive glycemic control as a ‘legacy effect’ in newly diagnosed type 2 diabetes mellitus. In contrast, we have learned that excessive intervention aimed at strong glycemic control could cause unexpected cardiovascular death in patients who are resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 161 publications
1
1
0
Order By: Relevance
“…Another retrospective cohort study using Japanese hospital administrative data also indicated that SGLT2 inhibitors were more effective than DPP‐4 inhibitors in reducing hospitalization for heart failure and all‐cause mortality in patients with type 2 diabetes, particularly in those without a history of cardiovascular disease 18 . These results reaffirm the importance of SGLT2 inhibitors as a valuable medical intervention in line with recent diabetes treatment recommendations to reduce cardiovascular risk in Asia 19 , 20 .…”
supporting
confidence: 79%
“…Another retrospective cohort study using Japanese hospital administrative data also indicated that SGLT2 inhibitors were more effective than DPP‐4 inhibitors in reducing hospitalization for heart failure and all‐cause mortality in patients with type 2 diabetes, particularly in those without a history of cardiovascular disease 18 . These results reaffirm the importance of SGLT2 inhibitors as a valuable medical intervention in line with recent diabetes treatment recommendations to reduce cardiovascular risk in Asia 19 , 20 .…”
supporting
confidence: 79%
“…Two other trials are of major interest, in that they were conducted to elucidate the role of multifactorial intervention in patients with type 2 diabetes mellitus [ 13 , 14 ]: the Anglo-DanishDutch Study of Intensive Treatment In People with Screen Detected Diabetes in Primary Care (ADDITION)-Europe [ 15 ], and the Japan Diabetes Optimal Treatment study for 3 major risk factors of cardiovascular diseases (J-DOIT3) [ 16 ], both of which recruited more than 2,000 patients with less advanced microangiopathies.…”
Section: Introductionmentioning
confidence: 99%